Effects of timing of pre-exercise nutrient intake on glucose responses and intermittent cycling performance - Pritchett, K; Bishop, P; Pritchett, R; Kovacs, M; Davis, JK; Casaru, C; Green, M (South African Journal of Sports Medicine, 2008)
Objective. To evaluate the effects of two different pre-exercise feeding schedules (15 minutes and 60 minutes prior to exercise) of a mixed-nutrient nutritional bar on blood glucose levels and subsequent intermittent, high-intensity cycling performance. Methods. Ten moderately trained athletes participated in this counterbalanced, crossover, repeated measures study. Participants completed a 50-minute counterbalanced treatment intermittent exercise protocol. During one trial, participants consumed 400 ml water and a nutritional bar 15 minutes before the exercise session (15MPE). During another trial, participants consumed 400 ml water and a nutritional bar 60 minutes before the exercise session (60MPE). During a control trial (CON) participants consumed 400 ml water. Results. There were no significant differences in plasma glucose response at rest or during exercise among the three treatments (CON, 15MPE and 60MPE). There were no significant differences in mean power (MP) between the three trials. Conclusions. Pre-exercise nutrient feedings at 15 minutes or 60 minutes before exercise did not affect intermittent cycling performance or blood glucose concentration. These results suggest that the time of ingestion, within 1 hour prior to exercise, of a complex carbohydrate similar in composition and volume used in this study does not impact on performance. South African Journal of Sports Medicine Vol. 20 (3) 2008: pp. 86-90